1997
DOI: 10.1128/aac.41.12.2621
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequence analysis of two copies of a 23S rRNA gene from Helicobacter pylori and association of clarithromycin resistance with 23S rRNA mutations

Abstract: In this study, two identical copies of a 23S-5S gene cluster, which are separately situated within the Helicobacter pylori UA802 chromosome, were cloned and sequenced. Comparison of the DNA sequence of the H. pylori 23S rRNA gene with known sequences of other bacterial 23S rRNA genes indicated that the H. pylori UA802 23S rRNA genes are closely related to those of Campylobacter spp. and therefore belong in the proposed Proteobacteria subdivision. The 5'-terminal nucleotide T or A of the 23S rRNA is close to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
148
1
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(160 citation statements)
references
References 40 publications
(57 reference statements)
8
148
1
3
Order By: Relevance
“…Versalovic et al [10] have found that clarithromycin resistance in H. pylori is associated with the functioning of three point mutations leading to the substitution of adenine for guanine or cytosine: A2143G, A2143C, and A2144G. Later, new point mutations located at other positions in the 23S rRNA gene were described, which were also associated with resistance of the microbe to clarithromycin: A2115G, G2141A, A2143T, G2224A, C2245T, and T2289C [11][12][13][14][15]. Mutations in the bacterial gene 23S rRNA are dominant or codominant, i.e., the presence of a mutant allele in bacteria carrying two or more ribosome operons is sufficient for the life of bacteria at high macrolide concentrations [16].…”
Section: Mutationsmentioning
confidence: 96%
See 2 more Smart Citations
“…Versalovic et al [10] have found that clarithromycin resistance in H. pylori is associated with the functioning of three point mutations leading to the substitution of adenine for guanine or cytosine: A2143G, A2143C, and A2144G. Later, new point mutations located at other positions in the 23S rRNA gene were described, which were also associated with resistance of the microbe to clarithromycin: A2115G, G2141A, A2143T, G2224A, C2245T, and T2289C [11][12][13][14][15]. Mutations in the bacterial gene 23S rRNA are dominant or codominant, i.e., the presence of a mutant allele in bacteria carrying two or more ribosome operons is sufficient for the life of bacteria at high macrolide concentrations [16].…”
Section: Mutationsmentioning
confidence: 96%
“…The appearance of H. pylori clarithromycin resistance is connected with a decrease in macrolide affinity for ribosome due to the generation of point mutations in the 23S rRNA gene [10]. There are two copies of a 23S rRNA gene in the H. pylori genome [11]. Several mutations ( A2115C, G2141A, A2143C, A2143T, A2143G, and A2144G ) associated with resistance to clarithromycin have been identified in the peptidyl-transferase region of the V domain of the 23S rRNA gene, but mutations A2143G, A2143C , and A2144G were most frequently encountered [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mutagenesis study performed by Taylor et al [24] has confirmed that the A2142G and A2143G mutations are associated with clarithromycin resistance. A review by Mêgraud [13] of several studies worldwide demonstrated that 81.5% of the mutations in clarithromycin-resistant isolates were the A2142G or A2143C mutations.…”
Section: Discussionmentioning
confidence: 72%
“…tions in the peptidyltransferase-encoding region of 23S rRNA confers resistance to clarithromycin by decreasing the binding of clarithromycin to ribosomes in H. pylori [5]. Most findings show that the major point mutations are the adenine → guanine transition at either position 2142 (A2142G) or 2143 (A2143G), or the adenine → cytosine transition at position 2142 (A2142C) [6].…”
Section: Introductionmentioning
confidence: 98%